Influence of Textural Modification of Gel Food by Hydrocolloids to Flavor Perception - Wongprasert, Thanakorn; Suppavorasatit, Inthawoot (Journal of Food Technology, Siam University, 2019)
Flavor perception happens during food consumption. It is directly related to flavor release from food. There are factors affecting rate of flavor release include volatile compounds’ concentration, compositions, and structures of the foods. Therefore, texture modification of food can unavoidably affect flavor perception. Gel foods are textural modified by many methods, which using hydrocolloids to modify the texture is a common one. Each hydrocolloid gives different gel textures, which make them different in flavor release profiles since the food structures are changed. The occurrence of physical entrapments of flavors and/or interactions between flavors and food components can decrease the release of flavors from the foods. The gel food models should not be complex ones and should show various textures. Dairy-consisted gel food is usually selected as a model for several studies. The direct injection mass spectrometry (DIMS) is normally used to study the effect of food component and/or food texture on the release of flavors during mastication. In addition, using both instrumental and sensory evaluation techniques can help us be able to accurately understanding the release and perception of flavors in food and can further use in food product developments.